Isolated ZIC4 Antibodies and Autoimmune Encephalitis in a Microsatellite-Instability-High Metastatic Uterine Carcinosarcoma during Immune Checkpoint Inhibitor Treatment - Charalampakis, Nikolaos; Tsoukalas, Nikolaos; Kykalos, Stylianos; Tolia, Maria (Archives of Clinical and Medical Case Reports, 2019)
Paraneoplastic neurological disorders (PNDs) are a group of neurological disorders associated with neoplasm and are relatively rare, accounting for less than 1% of cancer cases. We present the case of a 58-year-old woman who was diagnosed with metastatic uterine carcinosarcoma and received the programmed cell death protein-1 inhibitor Pembrolizumab. The patient developed agitation, hallucinations and short-term memory loss, followed by seizures and progressive unresponsiveness. Intensive care support and ventilation were required. Given the high suspicion for autoimmune encephalitis, paraneoplastic antibody testing was requested that was strongly positive for ZIC4 antibodies solely. The unresponsiveness of our patient after immunosuppressive treatment inferred poor prognosis, and after a few days, the patient died. To the best of our knowledge, this is the first case of PND with multifocal neurologic deficits in a patient with isolated ZIC4 antibodies associated with uterine carcinosarcoma. Immunotherapy has been shown to precipitate underlying autoimmune diseases, leading to a wide variety of neurological symptoms including encephalitis. Our case highlights the importance of evaluating serum/CSF onconeural antibodies in patients presenting with complex neurological symptoms to determine the possibility of paraneoplastic disorder.